A potential application for life-related organics detection on Mars by diffuse reflectance infrared spectroscopy. Issue 2 (February 2023) - Liu, Wang; Wu, Zhongchen; Chen, Wenxi; Jin, Guobin; Zhang, Wei; Lv, Xinfang; Yu, Pei; Zhao, Hong
Abstract: Life information searching is a hot point for Mars exploration. Ancient Mars was very likely to reach a habitable environment, and there was a real possibility of arising life on Mars. However, the current Mars has a harsh environment. Under such conditions, life materials on Mars are supposed to have taken the form of relatively primitive microbial or organic residues, which might be preserved in some mineral matrices. Detection of these remnants is of great significance for understanding the origin and evolution of life on Mars. The best detection method is in-situ detection or sample return. Herein, diffuse reflectance infrared spectroscopy (DRIFTS) was used to detect characteristic spectra and the limit of detection (LOD) of potential representative organic compounds with associated minerals. In view of high oxidation due to the electrostatic discharge (ESD) during dust actives on Martian surface. The degradation of organic matter by ESD process was studied under simulated Mars conditions. Our results show that the spectral characteristics of organic matter are significantly different from that of associated minerals. The different organic samples have different mass loss and color change after ESD reaction. And the signal intensity of infrared diffuse reflection spectrum can also reflect the changes of organic molecules after ESD reaction. Our results indicated that the degradation products of organics rather than organic itself are most likely to be founded on current Martian surface. Highlights: The spectral characteristics of potential Martian organics and simulated Martian minerals were recorded and analyzed. LOD of some organic compounds by IR was determined as a reference for life detection on Mars. The degradation of organic matter by ESD process was studied to understand the effect of dust storm discharge on the preservation of organic matter on Mars.